Perspective From a Youth Environmental Activist: Why Adults Will Listen to Youth in Politics - Hartley, Jenna M.; Higgins, Katelyn M.; Peterson, M. Nils; Stevenson, Kathryn T.; Jackson, Megan W. (Frontiers in Political Science, 2021)
This perspective article is divided between the account of an emerging youth political activist, Katelyn Higgins, and the subsequent collaborative research project she coordinated. After 10 years of experience in youth political action, Higgins worked with co-authors to develop a qualitative study to explore the processes underlying youth influence over local environmental policymaking. We present findings from that study to supplement her perspective. The study supported 4th and 5th grade teachers by offering a marine debris curriculum which encouraged students to share their knowledge with local community members through environmental activism events. At the first event, students aged 8–10 presented at a town hall meeting; we interviewed 16 adults in attendance. The second ‘event’ was a series of video PSAs (Public Service Announcements) in which students from across the state of North Carolina, USA, explained the harms of marine debris. Those PSAs were emailed to local officials; we conducted follow-up interviews with two officials. Four themes emerged to characterize how adults responded to youth environmental activism: young people were inspiring; adults want to support young people; and adults view young people as able to provide leadership for local action and challenge the establishment. Youth leaders and those looking to support them should be encouraged by these results, as they suggest adults, including local public officials, consider youth voices valuable and uniquely situated to foster productive political processes for addressing marine debris. Future research should continue to explore the degree to which positive feelings expressed by adults translate to action.